DEVELOPMENT OF INTERNATIONAL MIGRATION REGULATION MECHANISMS: A COMPARATIVE ANALYSIS OF GLOBAL AND REGIONAL SYSTEMS - Khakberdiev Mukhammad (International Journal of Business, Law and Political Science, 2024)
The regulation of international migration has become a critical global issue, necessitating cooperation across various governance frameworks. This paper conducts a comparative analysis of global and regional migration regulation systems, focusing on the roles played by key factors such as the International Organization for Migration (IOM), the Global Compact for Migration (GCM), and regional initiatives like the European Union (EU) and the African Union (AU). It highlights the strengths and limitations of these systems, utilizing statistics and case studies to illustrate their effectiveness. Global systems provide broad frameworks for cooperation but lack enforcement mechanisms, resulting in inconsistent adherence to international agreements. Conversely, regional systems offer tailored approaches that better address localized migration pressures but often struggle with political cooperation and uniformity. The analysis underscores the necessity for enhanced collaboration between global and regional systems to create a cohesive migration governance strategy that prioritizes human rights and effectively manages migration flows in an increasingly complex global landscape.